Studi Deskriptif Pengetahuan Ibu tentang Toilet Training pada Anak Usia Toddler (1-3 Tahun) di Paud Terpadu Citra Indonesia Banjarbaru - Nova Uly Simbolon; Agustine Ramie; Hammad , (Jurnal Forum Kesehatan, 2018)
Toilet training if not taught can cause children to be undisciplined, spoiled, and most importantly, children will experience psychological problems, children will feel different and cannot independently control defecation and urination. This study aims to determine the mother's knowledge about toilet training. The design of this study is descriptive. The study population was mothers who had toddler-age children (1-3 years) in Citra Integrated Integrated Education in Banjarbaru. Samples were taken using "Total Sampling" with a sample size of 31 mothers. Data is analyzed descriptively and presented in table form. The results of the study found that most of the mother's knowledge about toilet training in toddler age children was sufficient knowledge (41.9%). Good knowledge is found at the age of 31-40 years (45.45%). Good knowledge for mothers with higher education level (66.66%). Good knowledge for non-working mothers (60%). The results of the study found that sufficient knowledge of mothers who received information from TV/radio (38.88%). Increasing mother's knowledge about toilet training is needed both in formal and non-formal ways in collaboration with health workers